2017
DOI: 10.17161/jas.v0i0.5730
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Role Conflict on Job Satisfaction of Independent School Athletic Directors

Abstract: Role conflict and job satisfaction were measured for 56 independent school athletic directors whose schools were members of the New England Preparatory School Athletic Council (NEPSAC). Simple linear regression analysis was used to test if role conflict significantly predicted the NEPSAC athletic directors’ ratings of job satisfaction. Results of the simple linear regression revealed that job satisfaction was significantly predicted by role conflict. Results of a one-way analysis of variance revealed significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
3
0
1
Order By: Relevance
“…Meanwhile, an empirical study that supported the results of this study was a study conducted by Rajak [13] that the higher the work-family conflict, the lower one's job satisfaction. In addition, the results of research from Piko [14] and Conant [15] also showed that job dissatisfaction is caused by the high perceived work-family conflict.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, an empirical study that supported the results of this study was a study conducted by Rajak [13] that the higher the work-family conflict, the lower one's job satisfaction. In addition, the results of research from Piko [14] and Conant [15] also showed that job dissatisfaction is caused by the high perceived work-family conflict.…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned by Ireri (2016), an employee's degree of satisfaction is influenced by their motivating factors. Conant (2017) discovered that a lack of job responsibility is a factor in the employee's dissatisfaction and desire to leave their job. According to Modau et al (2018), an employee who has worked for an organization for a long period is less likely to depart.…”
Section: Job Satisfactionmentioning
confidence: 99%
“…An employee, therefore, who achieving self-actualization can have a high level of job satisfaction regardless of their jobs. Conant (2017) noted that dissatisfaction and wanting to leave the job are related to that employees are not getting a clear sense of work accountability. However, Ololo, Kalifa, and Tafese (2016) found that once an employee is serving for a long time, he is less willing to leave the company.…”
Section: Relationship Between Job Satisfaction and Turnover Intentionmentioning
confidence: 99%